Responding to medetomidine in Philadelphia: narrative summary of the public health response to a new psychoactive substance - TaReva Warrick-Stone; Serge-Emile Simpson; Phil Durney; Dennis Goodstein; Catherine Abrams; Raymond Bobb; Kory London; Daniel Teixeira da Silva (Addiction Science & Clinical Practice, 2026)
Abstract Background Despite the emergence of medetomidine as the dominant adulterant in Philadelphia’s illicit opioid supply, coordinated public health responses are limited or non-existent in the literature. Thus, we summarize a recent Summit in Philadelphia of outpatient and inpatient service providers who specialize in the care of persons who use drugs to discuss medetomidine response readiness and building ongoing community readiness for potential destabilizing drug supply changes. Purpose Describe a public health intervention that distributed information about practices across health care settings and mobilized key informants to identify and address barriers to treatment. Methods Descriptive summary of the in-person Summit organized by the Division of Substance Use Prevention and Harm Reduction at the Philadelphia Department of Public Health and the Health Federation of Philadelphia’s Substance Use Response, Guidance, and Education program to review cases of medetomidine-associated withdrawal across outpatient, emergency department, hospital, and substance use treatment settings. Results The authors reviewed the insights from attendees and grouped them into nine themes: overdose response, clinical recognition of withdrawal, monitoring withdrawal, treatment approach, patient care navigation, workforce development, testing and surveillance, mobile outreach, and reimbursement. The authors subsequently developed twelve summative recommendations to guide further public health interventions in Philadelphia and other communities where medetomidine may become a common adulterant in the drug supply. Conclusion The insights gained regarding medetomidine withdrawal management will be shared with community organizations providing services to people who use drugs in Philadelphia and clarify specific barriers and areas for ongoing support. Other communities experiencing shifts in drug supply may benefit from this knowledge and similar information sharing colloquiums.